PENERAPAN METODE MULTISENSORI DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN BAGI SISWA DISLEKSIA (STUDI KASUS DI SDN GROGOL 01 DEPOK) : Indonesia - Mila Karmila; Susilahati (STKIP Subang, 2025)
This research is motivated by the low reading ability of dyslexic students and delays in the learning process. Therefore, the application of multisensory methods through learning methods that use the senses of sight (visual), hearing (auditory), movement (kinesthetic), and touch (tactile) senses to enhance students' cognitive abilities, particularly in terms of early reading skills, by applying individualized learning approaches using these sensory modalities for dyslexic students at SDN Grogol 01 Depok. The purpose of this study is to determine the application of the multisensory method in improving early reading skills for dyslexic students using the senses of sight (visual), hearing (auditory), movement (kinesthetic), and touch (tactile). The approach used in this study is a qualitative approach with a case study research design and a descriptive nature, employing observation, interviews, and document analysis techniques. The results of this study indicate that the application of the multisensory method in improving early reading skills for dyslexic students, conducted through the senses of sight (visual), hearing (auditory), movement (kinesthetic), and touch (tactile), is effective. The method was implemented using alphabet boards, playdough, raised puzzles, picture books, and letter cards in a conducive, quiet, and peaceful environment. Through this implementation, students were able to recognize and distinguish letters, became more enthusiastic about learning, and were able to write letters.